Tricritical-point phase diagram in PrCu9Sn4. (13th April 2022) - Meng, Fanying; Ge, Min; Wei, Wensen; Rahman, Azizur; Liu, Wei; Wang, Aina; Zhao, Jun; Fan, Jiyu; Ma, Chunlan; Pi, Li; Zhang, Lei; Zhang, Yuheng
Abstract: Tricritical phenomenon appearing in multiple phases is a fundamental and attractive issue in condensed-matter physics. In this work, a field-modulated tricritical phenomenon is realized in single-crystal PrCu9 Sn4 . The magnetization under variable directions of field indicates strong magnetic anisotropy in PrCu9 Sn4, which reveals ferromagnetic coupling for H // c . A paramagnetic-to-ferromagnetic magnetic transition occurs with H // c at T C = 11.7 K, which is evidenced to be of a first-ordered type. The systematical study of the critical behavior gives that β = 0.195(8), γ = 0.911(1), and δ = 0.0592(1) for H // c consistent with a tricritical mean-field model, which suggests a field-modulated tricritical phenomenon. A detailed H − T phase diagram around the tricritical point (TCP) is constructed for single-crystal PrCu9 Sn4 for H // c, where ferromagnetic state, forced ferromagnetic phase and paramagnetic state meet at the TCP ( H tr = 799 kOe, T tr = 11.3 K). The single-crystal PrCu9 Sn4 supplies a platform to deep investigate the field-modulated magnetic couplings and tricritical phenomenon.